The tribological behaviour of aluminium matrix composites - Wilson, Scott (Centre for Materials Engineering, 2016)
Metal matrix composites consisting of 6061 and 2014 aluminium alloys, reinforced with 10%, 15% and 20% alumina particulates and a 6061 alloy reinforced with 20% SiC particulates, have been characterised in terms of their behaviour under various tribological conditions. In abrasive environments, the wear behaviour of each composite is dominated by their ability to resist indentation by hard particles. Abrasion against fine grit particles leads to a reduced load per abrasive particle and a correspondingly significant reduction in wear loss. Reciprocating sliding wear tests, conducted in an aqueous environment and against hardened steel counterfaces, displayed composite wear rates that were up to three orders of magnitude below those of their monolithic alloys. This is attributed to the increased resistance to surface shear provided by the reinforcing particulates themselves and their constraining effects on the matrix. The particulates become load bearing and protect the matrix by reducing the metal to counterface adhesive wear. However, the counterface wear increases due to the interaction with the hard reinforcements. Transmission electron microscopy of the worn composites reveal the formation of a transfer layer and subsurface dislocation structures which are similar to those found in metals subjected to low amplitude fatigue. In contrast to the results for abrasive and sliding wear, the composites show increasingly inferior cavitation and solid particle erosion resistances with increasing volume fractions of particulates. This depreciating effect was especially evident for particle erosion and can be related to the inability of metal matrix composites to accommodate the increments of strain which accompany erosive processes. The mechanisms responsible for the various performances have been studied by scanning electron microscopy, optical microscopy and transmission electron microscopy. An attempt is made to reconcile the steady state wear rates of the reinforced and unreinforced alloys with their observed wear modes, microstructures and bulk mechanical behaviour.